Pemenuhan Gizi Keluarga melalui Budidaya Tanaman Sayur dengan Hidroponik Sistem Sumbu dari Botol Plastik Bekas Fulfilling Family Nutrition through Leafy Greens Cultivation with Hydroponics Wick System using Used Plastic Bottles - Mulyana, Jeane Siswitasari; Anisa, Hida Arliani Nur; Imaniar, Lisana Husna; Ariyanti, Yanti; Adhha, Nurul; Sattia, Ana; Hidayah, Nur (Farmers: Journal of Community Services, 2025)
Wick system is an easy-to-do and energy-efficient hydroponic system. Used plastic bottles can be used as planting media, thereby reducing the amount of plastic waste. Pahawang Village is facing the problem of plastic bottle waste and there has been minimal effort to reduce and manage the plastic waste. Training in leafy greens cultivation using the wick system is very much needed by residents because the production can be consumed to meet the nutritional needs of the family. This activity aims to improve community knowledge and skills through training in vegetable cultivation with wick system using plastic bottle waste. The training succeeded in increasing the understanding and skills of participants regarding cultivation with the hydroponic wick system. There are several factors that drive this outcome, including the easy-to-understand content of material presentation, the easy wick system, and the motivation of the participants. Continuous community assistance needs to be carried out as a follow-up so that cultivation efforts can be continued. In that case, the community can generate economic benefits after fulfilling the nutritional needs of the family.